Vaccine-preventable haemophilus influenza type B disease burden and cost-effectiveness of infant vaccination in Indonesia - Gessner, Bradford D; Sedyaningsih, Endang R; Griffiths, Ulla K; Sutanto, Agustinus; Linehan, Mary; Mercer, Dave; Mulholland, Edward Kim; Walker, Damian G; Steinhoff, Mark; Nadjib, Mardiati (The Pediatric infectious disease journal, 2008)
Most of Asia, including Indonesia, does not use Haemophilus influenzae type b (Hib) conjugate vaccines. We estimated total vaccine-preventable disease burden and the cost-effectiveness of Hib conjugate vaccine in Indonesia. Hib pneumonia and meningitis incidences for children with access to health care were derived from a randomized vaccine probe study on Lombok Island, Indonesia during 1998-2002. Incidences were adjusted for limited access to care. Health system and patient out-of-pocket treatment cost data were collected concurrent with the probe study. For Hib vaccine in monovalent and combined (with DTP-HepB) presentations, we used 2007 UNICEF vaccine prices of US$3.30 and $3.75 per dose. For the 2007 Indonesian birth cohort, Hib vaccine would prevent meningitis in 1 of every 179 children, pneumonia in 1 of every 18 children, and 4.9% of mortality among those younger than 5 years. The total incremental societal costs of introducing Hib vaccine in monovalent and pentavalent presentations were, respectively, US$11.74 and $8.93 per child vaccinated. Annual discounted treatment costs averted amounted to 20% of pentavalent vaccine costs. For the pentavalent vaccine, the incremental costs per discounted death and disability adjusted life-year averted amounted to US$3102 and $74, respectively, versus $4438 and $102 for monovalent vaccine. Routine infant Hib vaccination would prevent a large burden of pediatric illness and death in Indonesia. Even without external funding support, Hib vaccine will be a highly cost-effective intervention in either a monovalent or pentavalent presentation based on commonly used benchmarks.